Tuan Guru: The Cape Muslim Philosophy Education System - Marasabessy, Bunyamin (UI Scholars Hub, 2004)
Tuan Guru Imam Abdullah ibn Qadhi Abd al-Salam is the Scholar of Islam who had an important role on the Islamic development in South Africa. He comes from Tidore (North Maluku) who exiled to the Cape in 1780 by the Dutch Colonial becouse of his oppsite to Dutch Colonial’s policy of monopoly, slavery, and forced labour. While in prison on his exiled at the Cape Town, he completed a number of magnum opus, i.e. Ma”rifah al-Islam wa al-Iman, a manuscript contain with qalam (Word of God), tauhid (Ones of God), and fiqh (Study of laws partaining to ritual obligation). After his bandaging, he establish a madrasah to educate the slaves and free blacks of the Cape who had become Muslim. The Muslim education in the Cape bassed on the Ash’ari concepts of takdir, iradah, taqwah, iktisab, qadha and qadhar. Thes concept had make as a basic in formation of muslim personality.